Magnetothermally-controllable coating for scattering and absorption in the terahertz spectral regime - Hamad M. Alkhoori; Noura N. Alderei; Aryam S. Alshamsi (Heliyon, 2024)
Plane-wave scattering and absorption characteristics of a spherical core composed of an isotropic material, and covered by InSb spherical coating are investigated in the terahertz spectral regime. The InSb coating is subjected to a magnetostatic field; hence it is a gyrotropic, uniaxial dielectric material comprised of two parameters: temperature and magnetostatic field. It is seen that the interplay of these two parameters can modify the various scattering efficiencies, depending on (i) the frequency of the incident plane wave, (ii) the incident plane-wave orientation with respect to the magnetostatic field's direction, and (iii) the identity of the core material. In particular, for a fixed orientation of the incident plane wave, the impact of the temperature and the magnetostatic field on the total scattering and the backscattering efficiencies becomes more pronounced at higher frequencies, compared to lower frequencies. The absorption efficiency, on the other hand, is strongly dependent upon these two parameters, regardless of the frequency. On fixing the two parameters of InSb, the role of the orientation of the incident plane wave with respect of the magnetostatic field' direction emerges in some spectral regimes for the total scattering and absorption efficiencies, and in high-frequency spectral regimes for the backscattering efficiency. These hold true for dielectric core, as well as for conductive core.